A comparative study on wear and corrosion behaviour of HVOF- and HVAF-sprayed WC–10Co–4Cr coatings. (2nd January 2017) - Liu, Y.; Liu, W.; Ma, Y.; Meng, S.; Liu, C.; Long, L.; Tang, S.
Abstract : In this work, WC–10Co–4Cr coatings were separately deposited on 300M steel by high-velocity oxygen fuel (HVOF) and high-velocity air fuel (HVAF) spraying processes. Microstructure, porosity, micro-hardness, bonding strength, wear and corrosion resistance of the coatings after different processing were investigated and compared. The result shows that dense and homogeneous microstructure existed in both two WC–10Co–4Cr coatings. Owing to lower temperature flames and higher particle velocity in the HVAF process, the HVAF-sprayed WC–10Co–4Cr coating exhibited less decarburisation, lower porosity (0.74%), higher micro-hardness (1162 HV0.3 ) and bonding strength (74.68 MPa) than HVOF-sprayed WC–10Co–4Cr coating. In addition, wear and corrosion resistance of these two coatings were evaluated by sliding wear test and electrochemical corrosion test. The HVAF-sprayed WC–10Co–4Cr coating also exhibited excellent wear resistance and superior corrosion property than HVOF-sprayed WC–10Co–4Cr coating.